Update on medical treatment of uterine fibroids. (September 2017) - Faustino, Fátima; Martinho, Margarida; Reis, José; Águas, Fernanda
Abstract: Objectives: In this review paper, the pros and cons of the available pharmacological options for the treatment of uterine fibroids are explored, including oral progestogens, levonorgestrel intra-uterine device, gonadotropin-releasing hormone analogs and progesterone receptor modulators with an emphasis on ulipristal acetate. Study design: The choice of the appropriate therapeutic approach for uterine fibroids depends on several factors, including women's age, parity, childbearing aspirations and wish to preserve fertility, extent and severity of symptoms, size, number and location of myomas, risk of malignancy and proximity to menopause. Some treatment algorithms have been proposed for uterine fibroids, considering both efficacy and safety data from clinical trials, and women characteristics and choices. Therefore, we propose two optimized treatment algorithms for the treatment of uterine fibroids, one for the treatment of uterine fibroids in women of reproductive age with the desire to spare reproductive capacity, and another for the treatment of uterine fibroids in women >40 years with no desire for pregnancy. Results: Symptoms associated with uterine fibroids may significantly impair a patient quality of life. Therapy includes surgery, which may range from a hysterectomy to several other uterus-sparing techniques and several different types of pharmacological therapies. Studies with ulipristal acetate have provided a change of paradigm in the treatment of uterine fibroids, demonstrating the efficacy and favorable tolerability profile, not only for the preoperative treatment of moderate to severe fibroid-associated symptoms, but also, and very importantly, for the long-term medical management of patients with symptomatic fibroids.